Bond behavior of polymer- and mineral-impregnated carbon fiber yarns towards concrete matrices at elevated temperature levels. (October 2022) - Silva, Rebecca Mansur de Castro; Zhao, Jitong; Liebscher, Marco; Curosu, Iurie; Silva, Flávio de Andrade; Mechtcherine, Viktor
Abstract: The bond of textile reinforcements towards concrete matrices plays an important role in the mechanical performance of Textile Reinforced Concretes, and the textile impregnation material is a crucial factor. In this work, the bond between different carbon yarns towards a concrete matrix was evaluated at elevated temperatures. A lab-developed cement-based (C) and geopolymer (GP) Mineral-impregnated Carbon Fibers (MCF) and commercially available epoxy resin (EP) coated carbon yarns were assessed. Both MCF yarns yielded high tensile strength and modulus of elasticity, compatible with commercial EP yarns. The C-MCF yarn showed higher bond strength towards the matrix than the GP-MCF yarn, probably due to better chemical compatibility. The EP yarn yielded the strongest bond towards the matrix at room temperature. At elevated temperatures, the bond between the EP yarn and concrete matrix became considerably weaker, while the MCF yarns could maintain a sufficient bond up to 300 °C.